Parental stress and associated factors among parents of preterm neonates admitted at neonatal intensive care unit among selected governmental hospitals Addis Ababa, Ethiopia, 2022. An institution-based cross-sectional study - Tilahun, Befkad Derese (Frontiers in Psychiatry, 2024)
The birth of a preterm infant and their subsequent admission to the Neonatal Intensive Care Unit (NICU) is a distressing and challenging experience for parents. The stress experienced by parents can have a significant impact on their mental health, parenting behaviors, and the parent-infant relationship. Recognizing and addressing the stressors faced by parents in the NICU is essential for promoting their well-being and facilitating positive parent-infant interactions.Methods: A cross-sectional study was conducted at healthcare facilities. The participants for the study were selected using a systematic sampling method, where the sampling interval (K) was calculated for each hospital. Data collection involved the use of a pretested structured questionnaire administered by interviewers. The collected data was analyzed using the Statistical Package for the Social Sciences (SPSS) version 25.0. Simple and multivariable linear regression analyses were performed. Statistical significance was determined using a p-value of less than 0.05.The accompanying mother (β = 3.094, 95% CI: 3.615, 6.550), length of NICU stay greater than 10 days (β = 5.823, 95% CI: 1.759-9.887), the gestational week between 34 -37 weeks (β = -3.509, 95% CI: -6.358, -.659), parents with college degrees and above (β = -8.667, 95% CI: (-14.111,3.223), mothers who delivered via cesarean section (β = 2.468, 95% CI: -1.822, 4.759), parents without a history of neonatal NICU admission (β = -6.16, 95% CI: -11.69, -.63), and parents whose infant without ventilation (β = -2.755, 95% CI:. -5.492, -.0189) were significantly associated with parental stress.Parent in this setting revealed high levels of stress during their premature infants' NICU admission. The gestational week, educational status of the parents, mode of admission, and mode of delivery were found to have significant associations with parental stress. It is important for healthcare providers to recognize and understand the stress experienced by parents when caring for families with preterm infants in the NICU. They should provide support and assistance to parents as they navigate the challenges and stress that come with this situation.